COVID-19, HIV-Associated Cryptococcal Meningitis, Disseminated Tuberculosis and Acute Ischaemic Stroke: A Fatal Foursome - Bongomin F; Sereke SG; Okot J; Katsigazi R; Kandole TK; Oriekot A; Olum R; Atukunda A; Baluku JB; Nakwagala F (Infection and Drug Resistance, 2021)
Felix Bongomin,1,2 Senai Goitom Sereke,3 Jerom Okot,2 Ronald Katsigazi,1 Tadeo Kiiza Kandole,4 Anthony Oriekot,5 Ronald Olum,1 Angella Atukunda,6 Joseph Baruch Baluku,5 Frederick Nakwagala6 1Department of Medicine, School of Medicine, Makerere University College of Health Sciences, Kampala, Uganda; 2Department of Medical Microbiology and Immunology, Faculty of Medicine, Gulu University, Gulu, Uganda; 3Department of Radiology and Radiotherapy, School of Medicine, Makerere University College of Health Sciences, Kampala, Uganda; 4Infectious Diseases Institute, Makerere University College of Health Sciences, Kampala, Uganda; 5Division of Pulmonology, Kiruddu National Referral Hospital, Kampala, Uganda; 6Department of Medicine, Mulago National Referral Hospital, Kampala, UgandaCorrespondence: Felix BongominDepartment of Medical Microbiology and Immunology, Faculty of Medicine, Gulu University, Gulu, UgandaTel +256-784-523-395Email drbongomin@gmail.comBackground: Several viral, bacterial and fungal co-infections have been associated with increased morbidity and mortality among patients with COVID-19. We report a fatal case of severe COVID-19 pneumonia in a patient with a recent diagnosis of advanced HIV disease complicated by cryptococcal meningitis, disseminated tuberculosis and acute ischemic stroke.Case Presentation: A 37-year-old Ugandan woman was diagnosed with HIV infection 8 days prior to her referral to our center. She was antiretroviral naïve. Her chief complaints were worsening cough, difficulty in breathing, fever and altered mental status for 3 days with a background of a 1-month history of coughing with associated drenching night sweats and weight loss. The reverse transcriptase–polymerase chain reaction for SARS-CoV-2 of her nasopharyngeal swab sample was positive. Chest radiograph demonstrated military pattern involvement of both lungs. The serum and cerebrospinal fluid cryptococcal antigen tests were positive. Urine lipoarabinomannan and sputum GeneXpert were positive for Mycobacterium tuberculosis. Computed tomography of the brain showed a large acute ischemic infarct in the territory of the right middle cerebral artery. Regardless of the initiation of treatment, that is, fluconazole 1200 mg once daily, enoxaparin 60 mg, intravenous (IV) dexamethasone 6 mg once daily, oral fluconazole 1200 mg once daily, IV piperacillin/tazobactam 4.5 g three times daily and oxygen therapy, the patient passed on within 36 hours of admission.Conclusion: Co-infections worsen COVID-19 outcomes.Keywords: COVID-19, HIV, cryptococcal meningitis, stroke, tuberculosis, co-infection